Ação de diferentes grupos químicos de inseticidas sobre o desenvolvimento embrionário, emergência de Spodoptera frugiperda (Smith & Abbot, 1797) (Lepidoptera: Noctuidae) e seletividade à Vespidaes predadores - Soares, Walyson Silva (2018)
The insecticides with action on Spodoptera frugiperda (Smith & Abbot, 1797) eggs (Lepidoptera: Noctuidae) can be effective in controlling the pest and reducing its emergence. However, excessive use of insecticide causes negative impacts to natural enemies. Thus, it is necessary to use a physiological insecticide that is more toxic to the pest than to the natural enemies. The objective of this study was to evaluate the action of different chemical groups of insecticides on the embryonic development, emergence of Spodoptera frugiperda (Smith & Abbot, 1797) (Lepidoptera: Noctuidae) and selectivity to Vespity predators Protonectarina sylveirae (Saussure, 1854) and Brachygastra lecheguana (Latreille, 1824). The first experiment was conducted in a completely randomized design with four replicates. Ten insecticides from the chemical groups (Oxadiazine, pyrethroid, anthranilamide, oxime + benzoylurea methyl benzoylurea, benzoylurea, pyrethroid + anthranilamide, pyrazole analog and spinosyn) were diluted in water to obtain the concentration of active ingredient in the dose (100%). An airbrush was used to spray 1 mL of the insecticide solution (9 treatments) and 50 psi water (control) on the first layer of the S. frugiperda egg masses. The evaluations were performed when the eggs had ages of 72, 96, 120, 144 and 168 hours after laying. In each experimental unit, the number of emerged caterpillars was counted. Then, the rate of hatching of caterpillars was calculated. The second experiment was conducted in a completely randomized design in a 10 x 2 x 2 factorial scheme (Insecticide x concentration of active ingredient x species) with four replicates. Dilutions of ten insecticides of the chemical groups (Oxadiazine, pyrethroid, anthranilamide, oxime + benzoylurea methylcarbamate, benzoylurea, pyrethroid + antranilamide, pyrazole analogue and spinosyn) were performed to obtain the concentration of active ingredient in the dose (100%) and sub-dose (50%). The leaves of maize were immersed in insecticidal syrup (9 treatments) and water (control). The leaves were dried in the shade for thirty minutes and then packed in Petri dishes (9 cm in diameter and 2 cm in height). Twenty adult wasps per plaque were placed and then covered by a thin organza tissue held by elastics. After 24 hours, the percentage of dead wasps was evaluated. Methomyl + novaluron, chlorantraniliprole + lambda-cyhalothrin and deltamethrin reduced the hatch rate of S. frugiperda caterpillars and were highly toxic to wasps P. sylveirae and B. lecheguana in the dose (100%) and sub-dose (50%). The insecticide alpha-cypermethrin resulted in low action on the eggs of S. frugiperda and was highly toxic to the wasps P. sylveirae and B. lecheguana in the dose (100%) and sub-dose (50%). The insecticides novaluron, chlorantraniliprole, espinosade, clorfernapir and indoxacarbe presented little toxicity to the wasps P. sylveirae and B. lecheguana and low action on the eggs of S. frugiperda. It is concluded that the insecticides methomyl + novaluron, chlorantraniliprole + lambda-cyhalothrin and deltamethrin had satisfactory control of the egg phase of S. frugiperda and were not selective to P. sylveirae and B. lecheguana.